20.1: Invited Paper: High Performance Top‐Emission Inkjet Printed OLEDs with Printed Electron Transport Layer. (26th August 2021) - Wang, Shipan; Wang, Ziqi; Su, Liang; Dong, Ting; Zhuang, Jinyong; Fu, Dong
Abstract : High performance top‐emission inkjet printed (IJP) OLEDs have been successfully developed with printed electron transport layer (ETL). The major challenge of multilayer IJP OLEDs is that the solution deposition of the upper layer will cause penetration, dissolution, or intermixing of the under‐layer film. Through optimization of ETL ink formulation and employing the solvent‐resistant EML materials, the damage of the ink solvent to the EML film can be well alleviated.